2004
DOI: 10.1007/s00421-004-1145-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brief leg cooling after moderate exercise on cardiorespiratory responses to subsequent exercise in the heat

Abstract: We investigated the effects of brief leg cooling after moderate exercise on the cardiorespiratory responses to subsequent exercise in the heat. Following 40 min of ergometer cycling [65% peak oxygen uptake (VO(2peak))] at 35 degrees C (Ex. 1), seven male subjects [21.9 (1.1) years of age; 170.9 (1.9) cm height; 66.0 (2.0) kg body mass; 46.7 (2.0) ml kg(-1) min(-1) VO(2peak)] immersed their legs in 35 degrees C (control condition, CONT) or 20 degrees C (cooling condition, COOL) water for 5 min and then repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…The results of the present study indicate that all cold water immersion Water immersion and repeat cycling performance 437 protocols effectively enhanced the maintenance of repeat performance compared with active recovery; suggesting that the reduction in core temperature observed before the second exercise task was beneficial, supporting the notion of an anticipatory regulatory response to exercise in the heat. A decreased heart rate following pre-cooling strategies has been observed (Hayashi et al, 2004;Marsh & Sleivert, 1999;Olschewski & Bruck, 1988;Wilson et al, 2002) and the results of the present study support such a decrease. In the present study, heart rate was significantly reduced during 40 min of passive rest in the heat following all cold water immersion protocols compared with active recovery of the same duration.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the present study indicate that all cold water immersion Water immersion and repeat cycling performance 437 protocols effectively enhanced the maintenance of repeat performance compared with active recovery; suggesting that the reduction in core temperature observed before the second exercise task was beneficial, supporting the notion of an anticipatory regulatory response to exercise in the heat. A decreased heart rate following pre-cooling strategies has been observed (Hayashi et al, 2004;Marsh & Sleivert, 1999;Olschewski & Bruck, 1988;Wilson et al, 2002) and the results of the present study support such a decrease. In the present study, heart rate was significantly reduced during 40 min of passive rest in the heat following all cold water immersion protocols compared with active recovery of the same duration.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, cold water immersion has been used as a method of pre-cooling before exercise in an attempt to improve performance in hot and humid environmental conditions. Various studies have shown cold water immersion (Eston & Peters, 1999;Merrick et al, 1999) and pre-cooling (Hayashi et al, 2004;Kay et al, 1999;Marsh & Sleivert, 1999) to be effective, providing positive results for recovery and/or subsequent performance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This technique was found to lower core temperature by 2 1C (tympanic) more rapidly (6 min) than other techniques such as cold air spraying and cool water bath immersion (approximately 18 min- Weiner and Khogali, 1980). More recently, whole leg water immersion for 5 min at 20 1C after work in the heat has been shown to be effective in reducing thermal and cardiovascular strain in subsequent work (Hayashi et al, 2004). These methods of cooling which may generate less intense cold stimulus intensities at the skin than with hand immersion, therefore avoiding the potential reflexive reduction of skin blood flow, may be worth considering by the emergency services as alternative cooling techniques.…”
Section: Article In Pressmentioning
confidence: 94%
“…During prolonged dynamic exercise at a constant workload in the heat, minute ventilation ( _ VE) increases progressively, suggesting that the increase could be associated with increasing body temperature (Dempsey et al 1975;Fujii et al 2008b, c;Hayashi et al 2004Hayashi et al , 2006Nybo and Nielsen 2001). We recently reported that _ VE increases in proportion to increasing core temperature during dynamic exercise at 50% of peak oxygen uptake ( _ VO 2peak ), although there was a great deal of individual variability in the ventilatory response to increasing body temperature (Hayashi et al 2006).…”
Section: Introductionmentioning
confidence: 95%